Code-switching and translanguaging inside and outside the classroom: bi-/multilingual practices of high school learners in a rural Afrikaans-setting - Strauss, Stuart (Stellenbosch : Stellenbosch University, 2016)
Thesis (MA)--Stellenbosch University, 2016.